A preliminary analysis of lecturers’ empathy in mitigating challenges of developing English for specific academic purposes (ESAP) assessment materials / Norkhairi Ahmad …[et al.] - Ahmad, Norkhairi; Muhammad, Ahmad Mazli; Ismail, Syafini; Baharom, Harmi Izzuan (Universiti Teknologi MARA, 2021)
Running English for Specific Academic Purposes (ESAP) courses at tertiary institutions is becoming more challenging due to a number of factors and it leaves impact on lecturers’ emotions. Emotional dimension is among the aspects that significantly influences the way lecturers view assessments and their choice of assessment practices. This paper specifically looks at empathy as one emotional aspects present within lecturers as they undertake tasks of developing assessment materials and mitigate the challenges that they encounter. Six senior ESAP lecturers teaching engineering students at two engineering related universities reflected on this scenario via interviews and self-reflections. Their empathy in planning and developing assessment materials were elicited and scrutinized via qualitative approaches. All the lecturers exuded empathy based on professional grounds and directed towards essential learner factors and the intended ESAP course outcomes attainment. Empathy was found to be consistently demonstrated towards language learner factors and their language learning context that comprise aspects like background of students, language proficiency level, familiarity with language materials, current knowledge and skills required for test-taking. Such empathy for the best interest of the learners have induced careful and selective practices among the lecturers when preparing assessment materials. The presence of empathy in assessment practices appeared to be second nature to the lecturers and it helps to complement assessment best practices and upholds quality delivery of the ESAP courses. Empathy at a positive level has enabled the lecturers to embrace the spirit of assessment for learning where more time and efforts were devoted towards planning suitable assessments that promote understanding and mastery of the language, before going for the assessment of learning or summative assessments.